2021
DOI: 10.1038/s41598-021-02404-x
|View full text |Cite|
|
Sign up to set email alerts
|

Biodegradation and metabolic pathway of sulfamethoxazole by Sphingobacterium mizutaii

Abstract: Sulfamethoxazole (SMX) is the most commonly used antibiotic in worldwide for inhibiting aquatic animal diseases. However, the residues of SMX are difficult to eliminate and may enter the food chain, leading to considerable threats on human health. The bacterial strain Sphingobacterium mizutaii LLE5 was isolated from activated sludge. This strain could utilize SMX as its sole carbon source and degrade it efficiently. Under optimal degradation conditions (30.8 °C, pH 7.2, and inoculum amount of 3.5 × 107 cfu/mL)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Permanganate combined with bisulfite has been shown to have a rapid removal capacity for SMX; 59 however, ZrFe 2 O 4 @ZIF-8 exhibited a complete removal of SMX. Sphingobacterium mizutaii LLE5 has demonstrated capacity for removing SMX under optimal degradation conditions with a capacity of 93.87%, 60 which is lower than the efficiency (100%) demonstrated by ZrFe 2 O 4 @ZIF-8. A recent study reported bowl-like FeCuS@Cu 2 S@Fe 0 with excellent complete removal of SMX within 5 min of operation.…”
Section: Resultsmentioning
confidence: 83%
“…Permanganate combined with bisulfite has been shown to have a rapid removal capacity for SMX; 59 however, ZrFe 2 O 4 @ZIF-8 exhibited a complete removal of SMX. Sphingobacterium mizutaii LLE5 has demonstrated capacity for removing SMX under optimal degradation conditions with a capacity of 93.87%, 60 which is lower than the efficiency (100%) demonstrated by ZrFe 2 O 4 @ZIF-8. A recent study reported bowl-like FeCuS@Cu 2 S@Fe 0 with excellent complete removal of SMX within 5 min of operation.…”
Section: Resultsmentioning
confidence: 83%
“…S1 first transformed SMX through hydrogenation and then degraded via desulfurization. This pathway was observed during substrate degradation by Pseudomonas psychrophila HA-4 [14] and Sphingobacterium mizutaii [31]. Acinetobacter sp.…”
Section: Identification Of Metabolites and Degradation Of Metabolites...mentioning
confidence: 83%
“…Some bacterial strains, such as Pseudomonas psychrophila HA-4 [14], Acinetobacter sp. [17], and Sphingobacterium mizutaii LLE5 [31], which utilized SMX as the sole carbon source, have been reported. Achromobacter sp.…”
Section: Isolation and Identification Of Smx-degrading Bacteriamentioning
confidence: 99%
“…One of the most widely used antibiotics for human usage, animal production, and aquaculture is sulfamethoxazole (SMX) [5,6], which is also regularly found in aquatic environments [7,8]. SMX residues, on the other hand, are difficult to be removed and may enter the food chain, posing substantial dangers to human health [9].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most widely used antibiotics for human usage, animal production, and aquaculture is sulfamethoxazole (SMX) [5,6], which is also regularly found in aquatic environments [7,8]. SMX residues, on the other hand, are difficult to be removed and may enter the food chain, posing substantial dangers to human health [9].Given the current problem, sulfamethoxazole discharged into the aqueous environment is challenging to be treated. The risk to water ecology and the environment is rising along with the cumulative environmental concentration.…”
mentioning
confidence: 99%